Pengembangan Nilai Nilai Adat Nyuguh untuk Mereduksi Perilaku Narsistik Pada Siswa Smp Negeri 8 Jember - Hotimah, Hotimah; Isriyah, Mudafiatun; Rahmawati, Weni Kurnia (Guidance : Jurnal Bimbingan dan Konseling, 2025)
This research aims to develop a module-based intervention to mitigate narcissistic behavior among adolescents. Employing the Research and Development (R&D) method, this study follows the ADDIE model, comprising analysis, design, development, implementation, and evaluation phases. A total of 12 eighth-grade students participated in the field testing. Narcissistic behavior is characterized by excessive self-love, disregarding others' feelings and needs. If left unchecked, this tendency can evolve into an abnormal or unhealthy personality trait. This underscores the need for targeted character education strategies, such as incorporating Nyuguh cultural values. The overarching objective of this research is to develop Nyuguh cultural values as a character education strategy to reduce narcissistic behavior